2004
DOI: 10.1152/ajpregu.00214.2003
|View full text |Cite
|
Sign up to set email alerts
|

Bovine lactoferrin has a nitric oxide-dependent hypotensive effect in rats

Abstract: is a multifunctional protein that is found in milk, neutrophils, and other biological fluids. Under inflammatory conditions, LF production is increased in the periphery by neutrophils. However, the cardiovascular function of LF is still unknown. In the present study, we investigated the effect of bovine LF (BLF) on the mean blood pressure (MBP) and heart rate (HR) in urethane-anesthetized rats and the vascular function of BLF in the rat thoracic aorta. Intravenous injection of BLF produced dose-dependent decre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
31
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 43 publications
4
31
0
Order By: Relevance
“…In our study, urine volume increased up to 2.5 times higher than the basal volume when the rat received bLf at a dose of 30 mg/kg. Hayashida et al [11] reported that bLf causes a nitric oxide (NO)-dependent relaxation of smooth muscle in the rat's aorta, suggesting that bLf can affect the blood circulation in individual organs. The involvement of NO in the renoprotective effect in cisplatin-injected rats was supported by a treatment with L-arginine resulting in NO modulation [22].…”
Section: Discussionmentioning
confidence: 99%
“…In our study, urine volume increased up to 2.5 times higher than the basal volume when the rat received bLf at a dose of 30 mg/kg. Hayashida et al [11] reported that bLf causes a nitric oxide (NO)-dependent relaxation of smooth muscle in the rat's aorta, suggesting that bLf can affect the blood circulation in individual organs. The involvement of NO in the renoprotective effect in cisplatin-injected rats was supported by a treatment with L-arginine resulting in NO modulation [22].…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence that lactoferrin increases nitric oxide production (25 ). In fact, lactoferrin has been shown to affect peripheral opioid-mediated antinociception via nitric oxide (26,27 ).…”
Section: Discussionmentioning
confidence: 99%
“…Whey contains lactoferrin, an antioxidant and antiinflammatory iron binding protein (Conneely, 2001). Hayashida et al (2004) reported that lactoferrin consumption in rats results in hypotension. The BP decrease was through an endotheliumdependent vasodilation mediated by nitric oxide production and possibly via the central opioidergic system.…”
Section: Discussionmentioning
confidence: 99%